2001
DOI: 10.1034/j.1399-6576.2001.451016.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous prostaglandin E1 on pial vessel diameters and intracranial pressure in rabbits

Abstract: We conclude that PGE1 might be a suitable drug for induced hypotension in neurosurgery from the viewpoint of its small effect on the cerebral microvessels and ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Both hypotensive groups had significantly lower MAP from the normotensive group but were not significantly different from each other, potentially due to the heterogeneous response of individual animals to the two dosages of PGE 1 . PGE 1 was chosen to manipulate MAP because at dosages of 3.0 μg kg −1 min −1 , the agent has no effect on cerebrovascular tone and does not impair the CVR in rabbits (Miyabe et al 2001, Takenaka et al 2003 and in humans (Abe 1993, Abe andYoshiya 1993). Interestingly, we found that ICP did not change over the range of MAP tested, which facilitated the use of MAP as a direct correlate of CPP and allowed us to minimize the invasiveness of surgery in the majority of the experiments.…”
Section: Discussionmentioning
confidence: 89%
“…Both hypotensive groups had significantly lower MAP from the normotensive group but were not significantly different from each other, potentially due to the heterogeneous response of individual animals to the two dosages of PGE 1 . PGE 1 was chosen to manipulate MAP because at dosages of 3.0 μg kg −1 min −1 , the agent has no effect on cerebrovascular tone and does not impair the CVR in rabbits (Miyabe et al 2001, Takenaka et al 2003 and in humans (Abe 1993, Abe andYoshiya 1993). Interestingly, we found that ICP did not change over the range of MAP tested, which facilitated the use of MAP as a direct correlate of CPP and allowed us to minimize the invasiveness of surgery in the majority of the experiments.…”
Section: Discussionmentioning
confidence: 89%
“…It has been proposed that PGE1 may improve symptoms in patients with lumbar spinal canal stenosis by promoting blood flow in the cauda equina and nerve roots through its vasodilating and anti-platelet aggregating effects (Yoshihara, 2016). In addition, Miyabe et al (2001) showed that cerebral microvessel diameter in rabbits is increased by intravenous administration of PGE1. As our previous finding has shown that the VAs have the ability to increase their diameter as an adaptive response to BCCAO (Jing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…9 The scalp was incised and retracted, and the temporal muscle was removed. A hole approximately 8 mm in diameter was made in the parietal bone.…”
Section: Ma At Te Er Ri Ia Al Ls S a An Nd D M Me Et Th Ho Od Ds S mentioning
confidence: 99%